Pregnancy, fertility, and recurrence risk in corrected tetralogy of Fallot. Issue 6 (13th May 2005) - Meijer, J M; Pieper, P G; Drenthen, W; Voors, A A; Roos-Hesselink, J W; van Dijk, A P J; Mulder, B J M; Ebels, T; van Veldhuisen, D J
Abstract : Objective: To determine in women with surgically corrected tetralogy of Fallot the risk of pregnancy for mother and fetus, whether fertility was compromised, and the recurrence risk of congenital heart disease. Design: Data were collected from 83 patients through interviews and review of medical records. Results: In 29 patients 63 pregnancies were observed, of which 13 ended in an abortion. Fifty successful pregnancies were observed in 26 patients. During six successful pregnancies (12%) complications (symptomatic right sided heart failure, arrhythmias, or both) occurred. Both patients who developed symptomatic heart failure had severe pulmonary regurgitation. No clear relation between offspring mortality, premature birth or being small for gestational age, and cardiac characteristics of the mother was identified. Fifty seven patients were childless (41 (72%) voluntarily). Recurrence risk for congenital heart disease was 2.2%. Infertility was uncommon. Conclusions: Although complications did occur in five of 26 (19%) of the patients with a corrected tetralogy of Fallot, pregnancy was generally well tolerated in this largest report so far. No obvious predictors for maternal events or child outcome were determined, except for a possible relation between severe pulmonary regurgitation and symptomatic heart failure.